Acronyms, initialisms & abbreviations dictionary a guide to acronyms, abbreviations, contractions, alphabetic symbols, and similar condensed appellations - Hall, Linda D. (Gale virtual reference library, 2008)
Provides definitions of a wide variety of acronyms, initialisms, abbreviations and similar contractions, translating them into their full names or meanings. Terms from subject areas such as associations, education, the Internet, medicine and others are included.